A note in the Arabic Bible about the interconfessional conflict in Palestine in the late 17th century - Serge Frantsouzoff (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article studies a note in the Middle Arabic language found before the Book of Job in the second volume of the earliest copy of the complete Arabic Bible kept in the collection of the Institute of Oriental Manuscripts of the Russian Academy of Sciences. This note, the author of which is unknown, deals with the seizure by the Roman Catholics of those Holy Places in Jerusalem and Bethlehem which belonged to the Greek Orthodox; the seizure was made with consent from the Ottoman authorities. This event, which in fact happened in 1690, is in the note erroneously dated two years earlier. In 1922, the text of the note was published by Archimandrite Elĳ ah from Alexandria in a considerably edited version in accordance with the rules of Classical Arabic grammar. This edition was carried out on the basis of an inaccurate copy taken in 1908 from the above-mentioned manuscript of the Arabic Bible which at that time was kept in the monastery of Balamand near Tripoli in Northern Lebanon. As a result, the content of the note was distorted in certain places, which aff ected its Greek and French translations. In this article, the original text of the note is published for the first time. The publication is accompanied by a Russian translation and commentaries. It identifies all political and church fi gures mentioned in the note, including the ambassador of France hidden under the nickname of Zamaria (in all probability, a distorted form of ce marquis).